Story-based scales: development and validation of questionnaires to measure subjective health status and cultural adherence in British Bangladeshis with diabetes. - Greenhalgh, T; Chowdhury, M; Wood, G (2006)
Questionnaires that measure subjective health status are increasingly used in clinical trials. But scales based on the quantification of subjective traits ("rate your feelings on a scale of 1 to 5") and initially developed in western population samples may not be valid for use in minority ethnic groups, even if accurately translated. The measurement of cultural adaptation and assimilation in immigrant groups is important for health research but has well documented methodological challenges. The aim of this study was to develop valid and reliable questionnaires to measure subjective health status and cultural adherence in a minority ethnic group, using the story as the unit of inquiry. The design was a multi-phase study involving (a) narrative interview, (b) vignette construction, (c) questionnaire development, and (d) questionnaire validation in relation to two scales (well-being and cultural adherence) in British Bangladeshis with diabetes. Using data from in-depth narrative interviews (i.e., a non-directive research technique in which the participant is invited to "tell me the story about your diabetes, starting with when you first noticed anything wrong", and the only prompts used are "tell me more about that" or "what happened next?"; Greenhalgh, Helman, and Chowdhury, 1998; Muller, 1999), we constructed culturally congruent vignettes to depict different subjective health states and behaviours. We refined these items in focus group interviews and validated the instruments on 98 Bangladeshi participants, randomly sampled from GP diabetes registers in inner London and interviewed by a Bangladeshi anthropologist. We used factor analysis to explore the underlying structure in the responses to questionnaire items, plus Cronbach alpha tests to measure internal consistency of scales. The questionnaires were acceptable and credible to Bangladeshi participants with diabetes. Ninety of 98 participants were able and willing to complete them with interviewer assistance. Following factor analysis, we produced two definitive instruments. The well-being scale was a single-factor model with four story-based items (measuring depression, anxiety, physical energy, and social activities), with a Cronbach's alpha of .92. The cultural adherence scale was a single-factor model with five items (measuring religious restrictions, ethnic practices, and social ties), with a Cronbach's alpha of .83. In conclusion, this study has produced two important outputs: (a) easy-to-administer, story-based questionnaires that measure well-being and cultural adherence, which are specific to British Bangladeshis with diabetes; (b) a general method for developing story-based instruments to quantify the subjective experience of illness and adherence to cultural norms, which potentially has applications beyond the study population.